Reflection of Ram Sewak: a sangam of the Gita and shri Ramcharitmanas - Tewari, Anirudh (Noida TreeShade Books, 2024)
Reflections of Ram Sewak$1 (BA Sangam of The Gita and Shri Ramcharitmanas delves into the eternal wisdom of two of India$1 (Bs most revered spiritual texts, The Gita and Shri Ramcharitmanas. This book presents 54 insightful musings, drawing on the author$1 (Bs extensive experience in public service and his spiritual journey to reveal how ancient teachings can guide us in modern life. It emphasises the enduring relevance of virtues like truth, forgiveness, self-control, contentment, and compassion. It is a profound exploration of the intertwining of the spiritual paths of Bhakti (devotion) and Gyan (knowledge) and offers readers a fresh perspective on how these can lead to a life of personal fulfilment and a world built on core human values. The book seamlessly integrates the wisdom of these two immortal spiritual masterpieces, mirroring the verses (chaupais and dohas) of Shri Ramcharitmanas with the shlokas of The Gita to bring into focus the eternalness of their messages. It invites readers of all age groups to discover their transformative power and progress to a life of integrity, love, compassion, and purpose.s
Keywords: Gita and Ramcharitmanas; IAS as an author